Hubungan Perilaku Hidup Bersih dan Sehat Terhadap Kejadian Diare Pada Anak Pra Sekolah - Nia Kurniawati; Ernawati Ernawati; Khalida Ziah Sibualamu (Malahayati Nursing Journal, 2026)
ABSTRACT Preschool children are considered a vulnerable group to infectious diseases, one of which is diarrhea. One of the key factors in preventing diarrhea is the practice of clean and healthy living behavior (PHBS), as it is directly related to children’s daily habits and their surrounding environment. This study aims to determine the relationship between clean and healthy living behavior (PHBS) and the incidence of diarrhea among preschool children at TK Al-Hidayah Pluit, Jakarta. The study employed a quantitative method with a cross-sectional approach. The population consisted of all preschool children at TK Al-Hidayah, totaling 151 children. Samples were taken using a stratified random sampling technique, with a total of 108 respondents. The research instruments included a questionnaire on PHBS and data on diarrhea incidence reported within the past three months. Data analysis was conducted using the Chi-Square test, with the strength of association measured through the Phi-Cramer’s coefficient. The findings revealed a statistically significant relationship between clean and healthy living behavior and the incidence of diarrhea among preschool children (p 0.001). The Phi-Cramer’s value of 0.493 indicated a moderate level of association. Children who practiced good PHBS were less likely to experience diarrhea, while those with poor PHBS were at higher risk of developing diarrhea. The study suggests increasing education for parents and educators on the importance of implementing PHBS from an early age through regular education and supervision of children’s daily routines to prevent diarrhea. Keywords: Child, Diarrhea, Health Behavior, Hygiene, Preschool.  ABSTRAK Anak prasekolah termasuk kelompok rentan terhadap penyakit menular, salah satunya diare. Salah satu faktor yang berperan dalam pencegahan diare adalah perilaku hidup bersih dan sehat (PHBS), karena berkaitan langsung dengan kebiasaan sehari-hari anak dan lingkungan sekitarnya. Penelitian ini bertujuan untuk mengetahui hubungan antara perilaku hidup bersih dan sehat (PHBS) dengan kejadian diare pada anak prasekolah di TK Al-Hidayah Pluit, Jakarta. Penelitian ini menggunakan metode kuantitatif dengan pendekatan cross-sectional. Populasi penelitian adalah seluruh anak prasekolah di TK Al-Hidayah yang berjumlah 151 anak. Sampel diambil menggunakan teknik stratified random sampling, dengan jumlah responden sebanyak 108 anak. Instrumen yang digunakan berupa kuesioner terkait PHBS dan data kejadian diare yang dilaporkan dalam tiga bulan terakhir. Analisis data dilakukan menggunakan uji Chi-Square dan pengukuran kekuatan hubungan menggunakan phi-cramer’s. Hasil penelitian menunjukkan adanya hubungan yang signifikan secara statistik antara perilaku hidup bersih dan sehat dengan kejadian diare pada anak prasekolah (p 0,001). Nilai phi-cramer’s sebesar 0,493 menunjukkan kekuatan hubungan dalam kategori sedang. Anak dengan praktik PHBS yang baik cenderung tidak mengalami diare, sedangkan anak dengan PHBS kurang memiliki risiko lebih tinggi terhadap kejadian diare. Saran dari penelitian ini adalah peningkatan edukasi kepada orang tua dan tenaga pendidik mengenai pentingnya penerapan PHBS sejak dini dalam edukasi dan pengawasan rutin. kehidupan anak, guna mencegah penyakit diare.  Kata Kunci: Anak, Diare, Perilaku Kesehatan, Kebersihan, Prasekolah.